The dual role of innate immunity in antiphospholipid syndrome and systemic lupus erythematosus. (October 2014) - Salem, D; Subang, R; Laplante, P; Levine, JS; Rauch, J
Antiphospholipid syndrome (APS), as a primary disease or a secondary syndrome in systemic lupus erythematosus (SLE), is characterized by the presence of antiphospholipid antibodies (aPL) and a clinical event. It is likely that both genetic and environmental factors lead to the development of aPL and progression to disease. However, the precise mechanisms are not known. We hypothesize that innate immune activation plays a dual role in APS and SLE, both in the production of aPL (i.e. "initiation" phase) and in the development of a clinical event (i.e. "effector" phase). We have shown that mice immunized with certain phospholipid-binding proteins (e.g. β2-glycoprotein I (β2GPI)), plus a concomitant trigger of innate immunity (e.g. a toll-like receptor 4 (TLR4) ligand), produce a strong β2GPI-reactive T cell response, resulting in high levels of aPL as well as other SLE autoantibodies. We propose that β2GPI, through its interaction with apoptotic cells, permits B cell epitope spread to multiple SLE autoantibodies. Innate immune activation is also implicated in a murine model of aPL-enhanced thrombus formation. This dual role of innate immune activation provides new insight into the mechanisms involved in the initiation of aPL and other SLE-related autoantibodies, as well as the development of aPL-mediated disease.